Metalloproteases Cleave the Urokinase-Type Plasminogen Activator Receptor in the D1-D2 Linker Region and Expose Epitopes not Present in the intact Soluble Receptor - Andolfo, Annapaola; English, William R.; Resnati, Massimo; Murphy, Gillian; Blasi, Francesco; Sidenius, Nicolai (Thrombosis and Haemostasis, 2002)
Proteolytic cleavage of the urokinase plasminogen activator receptor (uPA(R)) prevents the binding of uPA and vitronectin while generating biologically active uPAR fragments. We have recently shown that matrix metalloproteinase-12 (MMP-12) releases cellular uPAR-antigen from stimulated human micro-vascular endothelial cells providing a novel feedback mechanism between the plasminogen activation and MMP systems. We now show that MMP-12 and other MMPs directly and efficiently cleave uPAR at the Thr86||Tyr87 peptide bond located in the linker region connecting uPAR domains 1 and 2, releasing the major ligand binding domain 1 from the rest of the receptor. The possible biological importance of uPAR cleavage by MMPs is supported by the observation that also murine uPAR is cleaved by MMP-12 (at the Pro89||Gln90 peptide bond), despite the limited sequence homology between the linker regions. Using an antibody raised against the human uPAR linker region we show that this region of uPAR, which contains the chemotactic SRSRY epitope, is exposed upon MMP cleavage.
Keywords: uPAR; MMP; cleavage; fragments